(untitled) (Ameghiniana, 2013)
The microflora comes from the locality of Paganzo, 44 km WSW from Patquía (La Rioja). It belongs to the lower member of the Lagares Formation of the Paganzo Group. In the present paper sporomorphs referred to the infraturma Laevigati, Apiculati and incertae sedis belonging to twenty species are described. One genus (Lrmosporites), seven species and one variety (Calamospora multiplicata, Phylothecotriletes? aggregatus, Retusotriletes anfractus, R. simplex varo riojanensis, Anapiculatisporites? rallus, A.? variornatus, Apiculatasporites caperatus, Irmosporites circumpolaris.) are new. The age of this Carboniferous microflora will be discussed after all the collected samples are studied and the results published in next contributions.